1990
DOI: 10.1104/pp.94.4.1860
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a Sesquiterpene Cyclase in Cellulase-Treated Tobacco Cell Suspension Cultures

Abstract: The regulation of an elicitor-inducible sesquiterpene cyclase in tobacco (Nicotiana tabacum) cell suspension cultures was investigated. Sesquiterpene cyclase activity was absent from control cell cultures but induced to a maximum within 15 hours of cellulase addition to the cell cultures. When fungal elicitors are added to tobacco cell suspension cultures, the cultures cease sterol accumulation and instead synthesize and secrete sesquiterpenoids (23,25). Previous work correlated the decline in sterol biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…However, the level of cyclase mRNA translational activity in elicitor-treated cells was similar to that previously described (37). The cyclase translational activity was substantially reduced when elicitor-treated cell cultures were exposed to the calmodulin antagonists, 15 to 72% depending on antagonist and concentration used.…”
Section: Calcium/calmodulin Antagonists Suppresssupporting
confidence: 85%
See 2 more Smart Citations
“…However, the level of cyclase mRNA translational activity in elicitor-treated cells was similar to that previously described (37). The cyclase translational activity was substantially reduced when elicitor-treated cell cultures were exposed to the calmodulin antagonists, 15 to 72% depending on antagonist and concentration used.…”
Section: Calcium/calmodulin Antagonists Suppresssupporting
confidence: 85%
“…Immunoblot analysis of proteins separated by SDS-PAGE and specific immunoprecipitation of the radioactive cyclase and PAL proteins produced in vivo or in vitro have been described previously (37). The PAL antibodies were kindly provided by Dr. Lee Hadwiger (Washington State University, Pullman, WA).…”
Section: Immunological Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that inducible monoterpene (Steele et al, 1998), sesquiterpene (Vö geli and Chappell, 1990;Facchini and Chappell, 1992) and diterpene (Lois and West, 1990) biosynthesis are regulated at the level of transcription. The present studies are the first to indicate that the developmental regulation of monoterpene biosynthesis in secretory trichomes also resides largely at the level of gene expression.…”
Section: Transcriptional and Translational Regulation Of Monoterpene mentioning
confidence: 99%
“…The induction of EAS enzyme activity has been correlated with the absolute amount and the de novo synthesis of the enzyme protein (12). Changes in the de novo synthesis rate of the EAS protein were also correlated with changes in the EAS mRNA translational activity.…”
Section: Introductionmentioning
confidence: 95%